2017
DOI: 10.1038/s41598-017-12858-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related neurodegenerative disease associated pathways identified in retinal and vitreous proteome from human glaucoma eyes

Abstract: AbstarctGlaucoma is a chronic disease that shares many similarities with other neurodegenerative disorders of the central nervous system. This study was designed to evaluate the association between glaucoma and other neurodegenerative disorders by investigating glaucoma-associated protein changes in the retina and vitreous humour. The multiplexed Tandem Mass Tag based proteomics (TMT-MS3) was carried out on retinal tissue and vitreous humour fluid collected from glaucoma patients and age-matched controls follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 87 publications
(85 reference statements)
8
101
0
2
Order By: Relevance
“…There is established precedence in the literature confirming an association between CRYAB levels and disease with CRYAB showing modified expression in glaucoma models of high IOP (56,57). Additionally, analysis of the human vitreous humor proteome found that expression of numerous crystallin family proteins are significantly down-regulated in glaucomatous eyes (58).…”
Section: Myoc-cryab Interaction Impedes Protein Clearancementioning
confidence: 94%
“…There is established precedence in the literature confirming an association between CRYAB levels and disease with CRYAB showing modified expression in glaucoma models of high IOP (56,57). Additionally, analysis of the human vitreous humor proteome found that expression of numerous crystallin family proteins are significantly down-regulated in glaucomatous eyes (58).…”
Section: Myoc-cryab Interaction Impedes Protein Clearancementioning
confidence: 94%
“…One substantial shortcoming of quantification by isobaric labeling is the high cost of reagents. We and others have previously reported protocols in which the amount of TMT reagent recommended by the vendor was reduced (6 -10) and successfully applied such economically optimized labeling workflows to address a variety of biological questions (3,(11)(12)(13). However, details on the quantities and concentrations of reactants vary widely in the published literature and, to the best of our knowledge, no systematic evaluation of the influence of reducing TMT-to-peptide ratios on the overall labeling performance has been reported to date.…”
Section: Tir119001385mentioning
confidence: 99%
“…Deposits of amyloid β protein, synuclein, and pTau have been detected in the retinas of patients suffering from glaucoma. In addition, a recent proteomics study on the vitreous humor of glaucomatous patients found that 100 differentially regulated proteins are common to the pathophysiology of Alzheimer's disease [100]. Like neurodegenerative diseases, glaucoma produces neuroinflammatory reactions, particularly with regard to the activation of glial and microglial cells [101].…”
Section: Is Glaucoma a Neurodegenerative Disease?mentioning
confidence: 99%